2021
DOI: 10.1099/mic.0.001093
|View full text |Cite
|
Sign up to set email alerts
|

d-Serine induces distinct transcriptomes in diverse Escherichia coli pathotypes

Abstract: Appropriate interpretation of environmental signals facilitates niche specificity in pathogenic bacteria. However, the responses of niche-specific pathogens to common host signals are poorly understood. d-Serine (d-ser) is a toxic metabolite present in highly variable concentrations at different colonization sites within the human host that we previously found is capable of inducing changes in gene expression. In this study, we made the striking observation that the global transcriptional response of three … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 20 publications
5
16
0
Order By: Relevance
“…Relative expression and P -values for all amino acids tested can be found in Table S4 for CFT073, and S5 for Nissle 1917. Our RT-qPCR results corroborated the findings of our previous RNA-Seq study [21] and confirmed that D-Serine repressed expression of the colibactin synthesis genes in CFT073. In addition, D-Serine was shown to suppress clbB expression in Nissle 1917.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Relative expression and P -values for all amino acids tested can be found in Table S4 for CFT073, and S5 for Nissle 1917. Our RT-qPCR results corroborated the findings of our previous RNA-Seq study [21] and confirmed that D-Serine repressed expression of the colibactin synthesis genes in CFT073. In addition, D-Serine was shown to suppress clbB expression in Nissle 1917.…”
Section: Resultssupporting
confidence: 90%
“…Relative expression and P-values for all amino acids tested can be found in Table S4 for CFT073, and S5 for Nissle 1917. Our RT-qPCR results corroborated the findings of our previous RNA-Seq study [21]…”
Section: Expression Of the Genotoxin Colibactin Is Affected By D-and ...supporting
confidence: 91%
See 3 more Smart Citations